In this research, we study the taxation of intangibles, particularly the intellectual property (IP) at the international level. The main issue is the comparison of IP tax incentives in the United Kingdom and the Russian Federation. We also investigated the importance of R&D and intangible assets for companies. International activity of corporations raises in some cases the problem of double non-taxation due to gaps in legislation. This leads to the erosion of the tax base and we analyse it in the context of the Base Erosion and Profit Shifting (BEPS) Action Plan issued by OECD. This plan contains recommendations for countries on avoiding tax evasion by taxpayers. From our comparasion we conclude that some features of British taxation for innovative companies can be introduced into Russian tax system. But first, it is necessary to resolve internal problems in Russian tax legislation. - Shtuk, Ekaterina (2018)
Dissertação de Mestrado em Economia apresentada à Faculdade de Economia